(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Describe the current status of the working environment at X20 Joint Stock Company in 2024. Method: A cross-sectional descriptive study was conducted, using the results of working environment monitoring at 4 units under X20 Joint Stock Company. Results: The research results show that most of the samples of working environment monitoring did not exceed the allowable limits, in which the proportion of light, noise and cotton dust samples meeting the allowable standards were 85%, 84.7% and 70%, respectively. Most of the subjects had moderate psychological stress (60-88.3%), with no cases of excessive stress. Conclusion: Working environment factors at X20 Joint Stock Company generally met the standards; however, the workers’ psychological stress rate remained high. Therefore, further research is needed to determine a suitable method for assessing the level of psychological stress for this group of subjects.